1979
DOI: 10.1111/j.1748-1716.1979.tb06309.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of thiamine in neuromuscular transmission

Abstract: Pyrithiamine (50 mg/kg), a thiamine antagonist, decreased the muscle twitches of the rat masseter muscle at stimulation frequencies above 1 Hz 40--80 min after an i.v. injection. The post-tetanic potentiation (PTP) induced by nerve stimulation of the masseter muscle was abolished by pyrithiamine. Administration of thiamine restored the muscle twitches at stimulation frequencies above 1 Hz and the PTP. The muscle twitches elicited by direct muscle stimulation were not affected by pyrithiamine treatment. The abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Barchi considered it still possible that thiamine antagonists may interfere with the Na-transport system necessary for the action potential (1). Waldenlind was of the opinion that thiamine was important for the excitability of the nerve terminals by an effect on the active ion transport that was necessary for regeneration and maintenance of the membrane potential (17). Our results concerning the dorsal root do not support the view that thiamine reaches the axon membrane and nerve ending via axoplasmic transport (16), since it was impossible to observe AcPase and TMPase activity in the axoplasmic organelles such as microtubules, neurofilaments and endoplasmic reticulum.…”
Section: Discussioncontrasting
confidence: 56%
“…Barchi considered it still possible that thiamine antagonists may interfere with the Na-transport system necessary for the action potential (1). Waldenlind was of the opinion that thiamine was important for the excitability of the nerve terminals by an effect on the active ion transport that was necessary for regeneration and maintenance of the membrane potential (17). Our results concerning the dorsal root do not support the view that thiamine reaches the axon membrane and nerve ending via axoplasmic transport (16), since it was impossible to observe AcPase and TMPase activity in the axoplasmic organelles such as microtubules, neurofilaments and endoplasmic reticulum.…”
Section: Discussioncontrasting
confidence: 56%
“…A previous study using the smooth muscles of the gastric fundus and circular layer of the distal colon of guinea pigs reported that thiamin evoked depolarization in the smooth muscle strips as well as augmented the amplitude of inhibitory synaptic potentials and postinhibitory depolarization [36]. Furthermore, other studies suggested that thiamin is an integral component of synaptosomal membranes [37][38][39][40]. These findings suggested that thiamin plays a role in the mammalian neuromuscular transmission of ICCs to modulate contractions of the small intestine.…”
Section: Discussionmentioning
confidence: 87%
“…Another study suggested that thiamine is an integral component of synaptomal membranes 29 . A role of thiamine in mammalian neuromuscular transmission has also been suggested in other studies 30 . Taken together, all those data suggest that thiamine may have a specific, coenzyme-independent role in synapses.…”
Section: Thiamine-binding Proteinsmentioning
confidence: 81%